Candidatus Bartonella merieuxii, a potential new zoonotic Bartonella species in canids from Iraq. - Bruno B Chomel; Audrey C McMillan-Cole; Rickie W Kasten; Matthew J Stuckey; Shingo Sato; Soichi Maruyama; Pedro P V P Diniz; Edward B Breitschwerdt (Public Library of Science (PLoS), 2012)
Bartonellae are emerging vector-borne pathogens infecting erythrocytes and endothelial cells of various domestic and wild mammals. Blood samples were collected from domestic and wild canids in Iraq under the United States Army zoonotic disease surveillance program. Serology was performed using an indirect immunofluorescent antibody test for B. henselae, B. clarridgeiae, B. vinsonii subsp. berkhoffii and B. bovis. Overall seroprevalence was 47.4% in dogs (n = 97), 40.4% in jackals (n = 57) and 12.8% in red foxes (n = 39). Bartonella species DNA was amplified from whole blood and representative strains were sequenced. DNA of a new Bartonella species similar to but distinct from B. bovis, was amplified from 37.1% of the dogs and 12.3% of the jackals. B. vinsonii subsp. berkhoffii was also amplified from one jackal and no Bartonella DNA was amplified from foxes. Adjusting for age, the odds of dogs being Bartonella PCR positive were 11.94 times higher than for wild canids (95% CI: 4.55-31.35), suggesting their role as reservoir for this new Bartonella species. This study reports on the prevalence of Bartonella species in domestic and wild canids of Iraq and provides the first detection of Bartonella in jackals. We propose Candidatus Bartonella merieuxii for this new Bartonella species. Most of the Bartonella species identified in sick dogs are also pathogenic for humans. Therefore, seroprevalence in Iraqi dog owners and bacteremia in Iraqi people with unexplained fever or culture negative endocarditis requires further investigation as well as in United States military personnel who were stationed in Iraq. Finally, it will also be essential to test any dog brought back from Iraq to the USA for presence of Bartonella bacteremia to prevent any accidental introduction of a new Bartonella species to the New World.